Peran Identitas Daring dalam Pembentukan Citra Diri Remaja di Instagram: Sebuah Analisis Naratif - Riki Febriansyah; Nur Laila Isnatun Khotimah; Diah Natasya; Konto Iskandar Dinata (CV. Era Digital Nusantara, 2025)
This qualitative-interpretative study aims to analyze the narrative strategies employed by adolescents in constructing their online identity on Instagram and to explain the role of this narrative construction in the formation, reinforcement, or disruption of their internal self-image. Using a phenomenological method, data were collected from two active adolescent Instagram users (ages 16-20) in Palembang through in-depth semi-structured interviews, direct account observation, and visual documentation. The primary analysis technique involved Moustakas's phenomenological approach (Epoche, reduction, essence description), complemented by the Miles and Huberman model for data reduction and presentation, with data trustworthiness secured via triangulation and member checking. The results show that adolescent digital identity is formed through conscious self-curation and strategic privacy management, which directly affects their self-image negotiation with social validation. One subject maintained consistency with filtering, while the other built an idealized, more confident persona, leading to high dependence on external validation (likes) and increased susceptibility to social comparison and perfectionism pressures.